2020
DOI: 10.1021/acsomega.0c02786
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Reduction Mediated by Iron Catalysts: Mechanism and Intermediates That Guide Selectivity

Abstract: The reduction of carbon dioxide represents an ambitious target, with potential impact on several of the United Nations’ sustainable development goals including climate action, renewable energy, sustainable cities, and communities. This process shares a common issue with other redox reactions involved in energy-related schemes (i.e., proton reduction to hydrogen and water oxidation to oxygen), that is, the need for a catalyst in order to proceed at sustainable rates. Moreover, the reduction of CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…25 and 26 ). These results indicated that supplementary H + was indeed important for boosting the reduction efficiency of CO 2 to CO in the presence of [Cu(H 2 O)] + catalyst, in which H + from the coordinated H 2 O participated into the elimination of O atoms in CO 2 46 , 48 , 70 .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…25 and 26 ). These results indicated that supplementary H + was indeed important for boosting the reduction efficiency of CO 2 to CO in the presence of [Cu(H 2 O)] + catalyst, in which H + from the coordinated H 2 O participated into the elimination of O atoms in CO 2 46 , 48 , 70 .…”
Section: Resultsmentioning
confidence: 91%
“…16 ), 107 Ag, and 104 Pd (Supplementary Fig. 17 )-based reactions, allowed us to draw a definite conclusion that in the CO 2 RR process, the two O atoms in CO 2 were eliminated completely by losses of two molecules of H 2 O 46 , 48 , 70 , and the O atom in CO originated from the coordinated H 2 O. Moreover, H 2 18 O-labeling experiments in tandem with off-line GC-MS analysis were carried out to confirm the source of O atom in resulting CO from the reversed WGSR.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this sense, the hybrids wettability properties showed, as their structural formulation, that they could be necessary in order to observe phenol conversion, as can be evidenced by the fact that no reaction was observed under the same reaction conditions with γ-alumina spheres or FeAl spheres. Although values were far from full conversion, it is in the same range of those reported in the most common reaction, converting CO 2 to methanol in heterogeneous catalysis [ 52 , 53 ]. The porous distribution of the samples allowed for the phenol and CO 2 spread in the hybrids to the active sites by diffusion, while the aqueous solution was maintained outside the spheres due to their hydrophobicity properties created by the nanofibers and nanowhiskers-like growth, resulting in a biphasic media.…”
Section: Resultsmentioning
confidence: 65%
“…Neither double carboxylation nor meta-carboxylation product was detected. The formation of benzoic acid (0–6%), p-hydroxybenzoic (<1%) acid, and salicylic acid (0–10%), which presented an additional carbon in the molecular structure, should be related with the formation of C–C bonds by carboxylation [ 53 , 54 , 55 ]. The C@Al-923 and C@Al-1023 hybrids showed the highest relative amount of salicylic acid among carboxylation products (>90% of C7 compounds).…”
Section: Resultsmentioning
confidence: 99%